Absurd (anti)Heroes’ Journey toward Happiness: A Psychoanalytic Comparison between Arthur Fleck and Meursault - Rahim, Sifatur (Spectrum, 2023)
In his philosophical writing, The Myth of Sisyphus (1979), Albert Camus ponders the futility of the search for unity and absolute in this seemingly indifferent universe, and surmises that true happiness comes from accepting the meaninglessness of human existence. This particular school of thought is known as absurdism, and the narratives that fall under this discipline are referred to as absurdist texts. Camus not only expounds on the scopes of absurdism but also puts them into practice through his fiction. One such seminal absurdist novel by Camus is The Outsider (1987). In the novel, the writer delineates how the protagonist, Meursault, finds contentment by accepting his fate. A similar state of happiness is attained by Arthur Fleck, the protagonist of the film Joker (2019), when he accepts and assumes his proper place in society. From the onset, Fleck and Meursault may appear quite different from each other. However, upon closer inspection, the subtle similarities in their characteristics are perceptible, which bind them to a common threat of absurdity. It is undeniable that both Fleck and Meursault have committed homicide. Nonetheless, there is a greater force behind their acts than free will, and that is their unconscious drive. This paper explores the workings of the unconscious and its manifestation in Fleck and Meursault’s actions while explicitly commenting on the relationships with their respective mothers. This comparative study also highlights how both of them discover true happiness once they finally learn to accept their fate and reality. Spectrum, Volume 17, June 2022: 101-113